Research on the Development Experience of Resilient Cities in Guangdong Hong Kong Macao Greater Bay Area Take Zhuhai as an Example - Junzhang Chen; Liang Zheng; Yile Chen (PT FORMOSA CENDEKIA GLOBAL, 2022)
With the continuous construction of urbanization, climate change, crowd concentration, disasters and risks and other factors have led to the continuous exposure of urban vulnerability, so the issue of urban safety and urban resilience has become an unavoidable issue in urban planning and construction in today's society. Zhuhai, located in the southwest of the Pearl River Delta, is an important node city in the Guangdong-Hong Kong-Macao Greater Bay Area, and in recent years, the flood disasters caused by extreme climate have adversely affected Zhuhai's economic development and social level. Based on the concept and meaning of resilient city, this study summarizes the relevant experience of resilient cities in China, analyzes the difference between disaster prevention planning and traditional planning from the perspective of resilient city planning, technical means and ideas, and studies on the governance of the current planning status of resilient cities in China, and discusses the resilience assessment of urban disasters in Zhuhai under the support of the resilient city theory based on the Zhuhai sponge city drainage special planning project, and from the urban disaster prevention and mitigation policies and disaster relief. The three aspects of climate adaptation planning technology and the construction of Zhuhai Community Disaster Prevention Park put forward corresponding countermeasures conducive to zhuhai's economic development and people's living standards improvement, enhance urban resilience, and at the same time adopt regional innovation methods, learn from the relevant treatment methods and methods of disaster prevention and mitigation and relief planning under the concept of Shenzhen Resilient City, and provide reference value for Zhuhai's resilient urban planning research and even for the resilience development of typical coastal cities.